Anticholinergic activity disappears soon after the prescription of cholinesterase inhibitor. Issue 4 (2016) - Koganemaru, Taishi; Hori, Koji; Hosoi, Misa; Konishi, Kimiko; Hachisu, Mitsugu; Tomioka, Hiroi; Tani, Masayuki; Kitajima, Yuka; Inamoto, Atsuko
No abstract available